Urine Cadmium as a Risk Factor for Osteoporosis and Osteopenia: A Meta-Analysis - Li, Dong; Lin, HaoJie; Zhang, Min; Meng, Jing; Hu, LiYou; Yu, Bo (Frontiers in Medicine, 2021)
Background: As society ages, the incidence of osteoporosis increases. In several studies, cadmium (Cd) is thought to be related to osteoporosis. However, there are conflicting reports about the relationship between Cd and the risk of osteoporosis and osteopenia. Therefore, the purpose of this meta-analysis was to explore the relationship between Cd and osteoporosis and osteopenia. Methods: Through a review of the literature, articles published in PubMed as of December 2020 were identified and the references of related publications and reviews were reviewed. Ultimately, 17 eligible articles were selected to determine the relationship between blood and urine Cd concentrations for the risk of osteoporosis or osteopenia. In this study, we performed a classification analysis, heterogeneity test, subgroup analysis, and evaluated publication bias. Results: A total of 17 studies were included, including seven on blood Cd and 10 on urine Cd. By combining the odds ratio (OR) and 95% confidence interval (CI) for the lowest and highest categories, the odds ratio of blood Cd concentration that increased the risk of osteoporosis or osteopenia was OR 1.21 (95% CI: 0.84-1.58) and that of urine Cd concentration that increased the risk of osteoporosis or osteopenia was OR 1.80 (95% CI: 1.42-2.18), and the results of the subgroup analysis were also consistent. Conclusions: Our research showed that urine Cd concentration is associated with an increased risk of osteoporosis and osteopenia. In contrast, blood Cd concentration showed no significant relationship with osteoporosis and osteopenia. Therefore, compared to blood Cd concentration, urine Cd concentration can be used as a risk factor for osteoporosis and osteopenia.